Dislocation Avalanches in Compressive Creep and Shock Loadings - Alexander R. Umantsev (Metals, 2025)
Motion of dislocations is a common mechanism of plasticity in many materials. Acoustic emissions and stress bursts turned out to be integral parts of this mechanism. An adequate description of these processes is an important goal of the Materials Theory, which aims to describe the mechanical properties of materials and their reliability in service. In this article, a novel approach to dislocation plasticity capable of describing emission events and stress bursts is introduced, and computational experiments intended to model the processes of compressive creep and shock compression in samples of various makeup and sizes are discussed. It turns out that the emission events self-organize into dislocation avalanches, which propagate at a speed determined by the conditions of loading. In the compressive creep experiments, the avalanches arrange into slow-moving slip bands, while in the shock compression experiments the avalanches move faster than sound.